Early partial portal venous contrast enhancement in canine CT‐Angiography. Issue 6 (13th August 2020) - Earley, Naomi F.; Hall, Jon L.; Brown, Helen; Schwarz, Tobias
Abstract: Early partial portal vein contrast enhancement (EPoVE) during the late arterial phase is seen in CT angiography of dogs. Previously, it has been a finding attributed to arterioportal vascular anomalies. However, EPoVE may be a normal feature of venous return from abdominal organs. This prospective, descriptive study investigated the origin of EPoVE using four‐dimensional CT (4D‐CT). Sixteen dogs undergoing 4D‐CT for disease of the cranial abdomen were prospectively collected. Regions of interest were placed in the hepatic artery (HA), gastroduodenal vein (GV), extrahepatic portal vein (EHPV) cranial and caudal to the GV, and splenic vein (SV) caudal to its EHPV entry. Times to earliest, partial, full, and maximal vascular enhancement were recorded. A mixed model analysis of variance was used to compare time‐to‐contrast enhancement between vessels. The number, origin, and time of EPoVE were recorded if visible. A total of 24 EPoVE areas were observed in all dogs. Most dogs had either one (10/16) or two (5/16) areas of EPoVE. The origin of EPoVE was identified in 14 of 24 areas: the GV in five areas, cranial mesenteric vein in four areas, pancreatic branch of SV in three areas, and SV in two areas. The time‐to‐contrast‐enhancement was significantly different for the individual veins compared to the HA. EPoVE during the late arterial phase is a common phenomenon of early portal venous drainage of abdominal organs; it should not be interpreted as pathognomonic for arterioportal vascular anomalies, which should be diagnosed based on additional criteria.